Epidemiologie der Sportverletzungen - 25-Jahres-Analyse einer sportorthopädisch-traumatologischen Ambulanz - Steinbrück, K. (Sportverletzung Sportschaden, 1999)
In a 25-years period (1972-1997) 30,603 sportsmen, having a total of 34,742 sports related injuries, were treated in our outpatient-department specialized in sports orthopaedics and traumatology. All cases were systematically recorded and analysed right from the beginning. This is the most extensive clinical statistics currently known. The absolutely highest incidence rate of sports-related injuries is seen in common disciplines like soccer with 10,493 (34.3%), skiing with 3632 (11.9%), handball 2307 (7.5%), tennis 1643 (5.4%) and volleyball 1550 (5.1%). 3/4 were male. The distribution of age shows a significant peak between 20 and 29 years of age, whereas in women we found a wide plateau between 10 and 39 years. Compared to earlier investigations we have an increase of injuries in higher age. In 72.4% the lower extremities are mainly effected, followed by the upper extremities (21.8%) and the spine with 3.0%. With increasing tendency knee injuries take main part (36.6%--12,708 cases) followed by injuries of the ankle (19.9%--6920 cases), shoulder (7.7%), lower leg (7.0%) and fingers (5.8%). Main diagnosis were: distortion (32.6%); ruptures of ligaments and menisci (21.5%); fractures (10.5%) and lesions of muscles and tendons (8.8%). Comparing our 15- and 25-years studies we found an interesting significant increase of injuries in skiing, tennis and physical exercising by 25%, in cycling four times. New disciplines like squash, snowboarding, mountainbiking and inlineskating have been added. All together the number of injuries is distributed to 87 different disciplines. In 1998 26.7 million sportsmen (one third of the German population) were member of the German Sports Association (DSB). The number of annual accidents in sports and sporting spare time activities is estimated at about 1.5-2 million, that's 25-30% of all accidents. The analysis of almost 35,000 treated sports injuries and further evaluation of more than 5000 orthopaedic examinations of top athletes are useful for analysis comparing single disciplines.